Integration of Religious Values in Character Education in the Digital Era - Syukrin, Syukrin; Salahudin, Salahudin (Council: Education Journal of Social Studies, 2025)
The digital era poses significant challenges to character education, where technological advancements have both positive and negative impacts on individual moral development. Religious values, as the foundation of ethics and morality, play a critical role in character education to navigate this era. This study aims to explore the concept of integrating religious values into character education in the digital era, focusing on implementation strategies, challenges, and relevant solutions. Using a qualitative approach based on literature studies, the findings reveal that the integration of religious values can be facilitated through digital technologies, such as religion-based learning applications, social media for disseminating moral messages, and religious-themed educational games. Additionally, a religious character-based curriculum and the reinforcement of the roles of teachers and parents are crucial to ensuring success. However, this implementation faces challenges, including digital disparities, exposure to harmful content, and a lack of digital literacy among educators. To overcome these issues, strategic measures such as intensive teacher training, the development of moral value-based educational platforms, and cross-sector collaboration among governments, educational institutions, and religious communities are essential. In conclusion, the integration of religious values into character education in the digital era represents a strategic effort to cultivate a generation that is not only intellectually capable but also morally and spiritually resilient